The Implementation of ICT-Based Management Information Systems in Improving the Effectiveness of Administrative Services - Ardhi, Mohammad; Asis, Abdul; Bakri Alif, Muh.; Astuti, Astuti (DIDAKTIKA, 2023)
The need for information today is increasingly urgent in line with the currents of globalization that occur in all parts of the world. Implementation of a management information system based on information and communication technology is an absolute necessity and can provide a competitive advantage so that it becomes a high priority. In line with the development of science and technology, the demands of providing fast information are also increasing. The results of this study indicate that (1) a management information system can assist the administration of students in SMP Negeri 7 Watampone which is supported by adequate facilities and infrastructure and human resources that support administrative services (2) factors that support management information systems in Supporting student administration services is adequate school ICT equipment facilities, while the inhibiting factors are the down cycle and database maintenance (system renewal) during the data collection process. The implication of this research is that education personnel are expected to be required to be able to develop information systems to improve educational services by utilizing adequate technological innovations.